2019
DOI: 10.2147/jpr.s218332
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neuropathic Characteristics In Patients With Persistent Idiopathic Facial Pain</p>

Abstract: BackgroundPersistent idiopathic facial pain (PIFP) is a subtype of painful cranial neuropathies and other facial pains. The involvement of neuropathic mechanisms in PIFP, however, remains controversial. Using the Douleur Neuropathique 4 (DN4) questionnaire, the present study examined neuropathic characteristics in patients with PIFP.MethodsThe multi-institutional retrospective study collected the following clinical data from 205 consecutive patients with adult chronic pain: gender, age, BMI, diseases causing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, as PIFP is a very unusual diagnosis, higher sample sizes are difficult to acquire at a single institution. In fact, many studies of PIFP deal with comparable or smaller sample sizes [46][47][48][49]. Further, the outcomes may only be attributed to the specific therapeutic program at our institution although this is similar to corresponding programs in Germany.…”
Section: Limitationsmentioning
confidence: 89%
“…However, as PIFP is a very unusual diagnosis, higher sample sizes are difficult to acquire at a single institution. In fact, many studies of PIFP deal with comparable or smaller sample sizes [46][47][48][49]. Further, the outcomes may only be attributed to the specific therapeutic program at our institution although this is similar to corresponding programs in Germany.…”
Section: Limitationsmentioning
confidence: 89%
“…The authors concluded that there was a neuropathic component to PIFP [ 84 ]. Neuropathic characteristics were identified in 10% of PIFP subjects using a Douleur Neuropathique 4 (DN4) questionnaire, though the PIFP group was only compared to a cohort of post-herpetic pain patients and not to normal controls [ 85 ]. Notwithstanding, the data that suggests that at least some cases of PIFP are neuropathic in nature remains sparse.…”
Section: Discussionmentioning
confidence: 99%
“…According to the International Classification of Headache Disorders (3rd edition) classification (ICHD 3), it is defined as a recurring pain lasting more than 2 h daily for more than 3 months without any clinical neurological deficit and having poorly localized, dull aching, or nagging quality [ 2 ]. Neuropathic elements are believed to be involved, at least in some patients [ 3 ]. Treatment is often unsatisfactory, and typically invasive interventions are not considered effective.…”
Section: Introductionmentioning
confidence: 99%